2011
DOI: 10.5194/nhess-11-487-2011
|View full text |Cite
|
Sign up to set email alerts
|

Verification of surface minimum, mean, and maximum temperature forecasts in Calabria for summer 2008

Abstract: Abstract. Since 2005, one-hour temperature forecasts for the Calabria region (southern Italy), modelled by the Regional Atmospheric Modeling System (RAMS), have been issued by CRATI/ISAC-CNR (Consortium for Research and Application of Innovative Technologies/Institute for Atmospheric and Climate Sciences of the National Research Council) and are available online at meteo.crati.it/previsioni.html (every six hours). Beginning in June 2008, the horizontal resolution was enhanced to 2.5 km. In the present paper, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 30 publications
1
20
0
Order By: Relevance
“…Although RAMS has been implemented for a concrete area within the Western Mediterranean Basin, due to its similar climate and physical characteristics, we strongly believe that the results found is this study could be projected as well to other areas in the east coast of the Iberian Peninsula. In addition, the results reproduced in the present paper are analogous to those found in other Mediterranean Regions, using the RAMS model (Pasqui et al, 2004;Federico, 2011), and using other real-time mesoscale models (Bartzokas et al, 2010). Likewise, considering other areas with Mediterranean-type climate regimes, it has been found that atmospheric humidity is the main cause of elevated minimum temperatures in the summer (Gershunov et al, 2009).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Although RAMS has been implemented for a concrete area within the Western Mediterranean Basin, due to its similar climate and physical characteristics, we strongly believe that the results found is this study could be projected as well to other areas in the east coast of the Iberian Peninsula. In addition, the results reproduced in the present paper are analogous to those found in other Mediterranean Regions, using the RAMS model (Pasqui et al, 2004;Federico, 2011), and using other real-time mesoscale models (Bartzokas et al, 2010). Likewise, considering other areas with Mediterranean-type climate regimes, it has been found that atmospheric humidity is the main cause of elevated minimum temperatures in the summer (Gershunov et al, 2009).…”
Section: Discussionsupporting
confidence: 74%
“…More information about the software developed may be found in Gómez et al (2013). (Papanastasiou, 2010;Federico, 2011;Kotroni, 2011;Hernández-Ceballos et al, 2013). The statistical calculations carried out in both cases include the mean bias, root mean square error (RMSE) and the index of agreement (IoA) for the near-surface temperature, relative humidity and wind speed.…”
Section: Verification Proceduresmentioning
confidence: 99%
“…This overestimation was strongest for inland areas, where bias values up to 6 ºC were observed. Federico (2011), using an optimal interpolation analysis, reproduced low RMSE errors, around 2 ºC for minimum temperatures and slightly higher values for the maximum. In this study, the highest values both for Bias and RMSE were also located inland.…”
Section: Introductionmentioning
confidence: 99%
“…Within the Mediterranean area, different systems have been implemented to forecast extreme temperature, such as that of Bartzokas et al (2010) for northwest Greece, or the one implemented by Federico (2011) for the Calabria region (southern Italy). In the first case, using the MM5 model (Dudhia, 1993), the daily maximum air temperature was slightly overestimated by the model, while minimum temperature was significantly overestimated.…”
Section: Introductionmentioning
confidence: 99%
“…The R3 and R12 models share the same physical and dynamical parameterizations, which are as in Federico (2011), the only differences being their grids and horizontal resolutions. The R3 model uses two two-ways nested grids: the first grid has a horizontal resolution of 12 km and covers the Central part of the Mediterranean Basin, while the second grid extends over Central Italy with 3 km horizontal resolution.…”
Section: Methodsmentioning
confidence: 99%